2020
DOI: 10.1007/s12253-020-00820-4
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Interleukin-17RA Expression is Associated with Tumour Progression in Colorectal Carcinoma

Abstract: Interleukin-17 (IL-17) is a pro-inflammatory cytokine found in various cancers. Current evidence indicates that IL-17 plays a vital role in tumour initiation and progression in colorectal carcinoma (CRC) via binding with its receptor, IL-17RA. However, the association between clinicopathological features and presence of IL-17 and IL-17RA protein in primary CRC tissues remains unclear. This study also investigates the difference between the presence of IL17 and IL-17RA in the paired tumour tissues versus adjace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
7
2
Order By: Relevance
“…18 Another study revealed that the low or loss of IL-17RA is significantly associated with advanced stage tumors. 17 In the present study, no abnormality was found in endogenous IL-17RA expression in CRC tissues and adjacent normal tissues. Further, IL-17RA expression was significantly higher in CRC tissues than in adjacent normal tissues based on RT-qPCR and IHC (Figure 1A,B).…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…18 Another study revealed that the low or loss of IL-17RA is significantly associated with advanced stage tumors. 17 In the present study, no abnormality was found in endogenous IL-17RA expression in CRC tissues and adjacent normal tissues. Further, IL-17RA expression was significantly higher in CRC tissues than in adjacent normal tissues based on RT-qPCR and IHC (Figure 1A,B).…”
Section: Discussioncontrasting
confidence: 46%
“…Interestingly, the association between clinicopathological features and IL‐17RA expression in CRC remains unclear. According to previous studies, negative and lower expression levels of IL‐17RA are significantly associated with advanced stage and poor prognosis in patients with CRC 17,18 . However, ablation of IL‐17RA expression was found to reduce tumorigenesis in a sporadic CRC mouse model 10 .…”
Section: Introdctionmentioning
confidence: 95%
“…Another study revealed that the low or loss of IL-17RA is signi cantly associated with advanced stage tumors [17]. In the present study, no abnormality was found in endogenous IL-17RA expression in CRC tissues and adjacent normal tissues.…”
Section: Discussioncontrasting
confidence: 45%
“…Interestingly, the association between clinicopathological features and IL-17RA expression in CRC remains unclear. According to previous studies, negative and lower expression levels of IL-17RA are signi cantly associated with advanced stage and poor prognosis in patients with CRC [17,18]. However, ablation of IL-17RA expression was found to reduce tumorigenesis in a sporadic CRC mouse model [10].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the processes like "Factors promoting carcinogenesis in vertebrates" are directly associated with cancer while others such as the "Axonal and synaptogenic signaling" have also been associated with tumor promotion given their role in apoptosis inhibition, cell migration and neural network formation that sustain tumor growth (81)(82)(83). So far, studies aimed at evaluating the role of IL-17 in cancer have focused on the expression of IL-17RA or IL-17RC separately (84,85) without a systematic analysis of the heterodimer relevance, with few exceptions (63). In addition, under the idea that IL-17 can only signal through the canonical IL-17RA/RC receptor complex, the evaluation of IL-17RD expression in tumors in the context of IL-17 signaling has not been incorporated yet (86).…”
Section: Discussionmentioning
confidence: 99%